Policy Implementation of Law Number 16 the Year 2019 Regarding Marriage Age Limitation for the Prospective Brides in the Office of Religious Affairs, Gorontalo Utara Regency - djufri rauf; Zuchri Abdussamad; Karlina Napu (LP2M Universitas Bina Mandiri Gorontalo, 2023)
This research uses a qualitative approach and descriptive research by using data collection techniques through interviews, observation, and documentation. The data analysis technique was carried out with descriptive qualitative analysis techniques. The results of this research show that: The decisive factors in the policy implementation of this law that have not been fulfilled are 1) The limited human resources, 2) Facilities and infrastructure that has not been supported, 3) Frequent change of positions due to rolling (mutation) of the implementing section, 4) Limited budget allocated only through operational.